UV-cured glass solvent-free spraying adhesion solid color primer and preparation method thereof
By using UV-cured glass solvent-free spray-adhesive primer on the glass surface, a combination of polyurethane acrylate polymer, oligomer and epoxy acrylate, combined with epoxy-modified silane coupling agent, the problems of low coating efficiency and VOC emissions on the glass surface are solved, and efficient and environmentally friendly coating effects are achieved.
Patent Information
- Application Number
- CN202411592319.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to achieve efficient and mechanized coating on the glass surface, and there are problems of VOC emissions and long construction time during the curing process of traditional paint.
UV-cured glass solvent-free spray-adhesive primer, and a paint film with good adhesion to the glass is formed by combining polyurethane acrylate polymer, polyurethane acrylate oligomer and epoxy acrylate as the main curing resin, and combined with an epoxy-modified silane coupling agent.
It achieves good adhesion to the glass, has fast curing speed, is not prone to cracking in the later stage, and does not require solvent dilution during the construction process, zero VOC emissions, and significantly improves construction efficiency and environmental protection performance.
Abstract
Description
Technical Field
[0001] The invention relates to C09D and the field of coating compositions, and in particular to a UV-cured glass solvent-free spray-coated solid-color primer and a preparation method thereof. Background Art
[0002] The surface of glass is smooth, and the adhesion of primer on the glass surface is relatively poor. Generally, the glass needs to be pre-treated or a special construction process is used, and the process steps are complicated. The existing PU paint and low-temperature paint on the market cannot achieve fully mechanized and efficient painting. The production requires a lot of manpower and material resources, the product takes a long time to dry, and it takes a lot of factory space. Water-based primers also need to be cured at high temperature for more than 4 hours before sanding, which takes a long time to construct. In addition, VOC emissions are easily generated during the paint curing process, and environmental problems are serious. Therefore, it is very important to develop a solid color primer that can be used for large-scale construction, has good adhesion to glass, does not require solvent dilution, and has zero VOC emissions.
[0003] Chinese invention patent CN102643586A discloses a high-solid content quick-drying water-based white primer and its preparation method. It uses a metal cross-linked emulsion of acrylic acid with a core-shell structure. The prepared white primer has excellent polishing and filling properties, and the drying speed is fast. It can effectively close the wood gaps on the medium-density fiberboard substrate, stabilize the internal structure of the substrate, and the deformation rate of the substrate after construction is small, but the adhesion is low, which is not suitable for the coating of glass substrates. Chinese invention patent CN115449296B discloses an exterior wall anti-tear solid color primer and its preparation method. The solid color primer includes: acrylic acid-siloxane copolymer core-shell emulsion, which has a relatively small particle size and can significantly and efficiently penetrate into the substrate, improving the reinforcement and adhesion of the paint film to the substrate. The surface is a cyclosiloxane-treated silica dispersion, which can fill the gaps between the latex particles of the acrylic acid-siloxane copolymer core-shell emulsion, increase the compactness of the film, and improve the hardness of the paint film. However, it cannot be applied to the surface of the glass substrate, and the adhesion effect is not good. Summary of the invention
[0004] In order to develop a solid color primer that can be applied on a large scale, has good adhesion to glass, does not require solvent dilution during use, and has zero VOC emissions, the first aspect of the present invention provides a UV-cured glass solvent-free spray adhesion solid color primer, the preparation raw materials include component A and component B, the preparation raw materials of component A include, by weight: 40-60 parts of acrylic resin, 10-20 parts of diluent, 20-30 parts of powder, 5-10 parts of initiator, and 0.1-1 part of auxiliary agent; the component B includes at least a coupling agent.
[0005] As a preferred embodiment, the weight ratio of component A to component B is 100:(0.5-2).
[0006] As a preferred embodiment, the weight ratio of component A to component B is 100:(0.6-1.9).
[0007] As a preferred embodiment, the weight ratio of component A to component B is 100:1.
[0008] As a preferred embodiment, the acrylic resin includes one or a combination of polyurethane acrylate, epoxy acrylate, silicone-modified acrylate, and pure acrylate.
[0009] As a preferred embodiment, the polyurethane acrylate is a difunctional polyurethane acrylate, including a difunctional polyurethane acrylate oligomer and a difunctional polyurethane acrylate polymer.
[0010] As a preferred embodiment, the acrylic resin comprises a combination of a difunctional polyurethane acrylate polymer, epoxy acrylate and a difunctional polyurethane acrylate oligomer in a weight ratio of (30-40):(5-10):(5-10).
[0011] As a preferred embodiment, the weight ratio of the combination of the difunctional polyurethane acrylate polymer, epoxy acrylate and difunctional polyurethane acrylate oligomer is (30-35): (6-9): (6-9).
[0012] As a preferred embodiment, the weight ratio of the combination of difunctional polyurethane acrylate polymer, epoxy acrylate and difunctional polyurethane acrylate oligomer is 34.7:8:8.
[0013] A combination of polyurethane acrylate polymer, polyurethane acrylate oligomer and epoxy acrylate as the main curing resin can be used to prepare a solid color primer with good adhesion to glass, water resistance and wear resistance, and a fast curing speed. The paint film is not easy to crack in the later stage. The possible reasons are speculated to be: polyurethane acrylate polymer and polyurethane acrylate oligomer are both difunctional polyurethane acrylates with high molecular activity, which increases the curing speed, but volume shrinkage problems will occur during curing. By introducing high-viscosity epoxy acrylate, the rigidity of the resin molecular structure can be improved, the curing shrinkage of the coating can be reduced, and the leveling and fullness of the paint surface can be improved, and the sanding properties are also significantly improved.
[0014] As a preferred embodiment, the diluent is selected from at least one of tripropylene glycol diacrylate, 1,6-hexanediol diacrylate and dipropylene glycol diacrylate.
[0015] As a preferred embodiment, the particle size of the powder is ≤1 μm; the powder is selected from at least one of silicon dioxide, titanium dioxide, talc, and calcium oxide.
[0016] As a preferred embodiment, the particle size of the talc powder is 1250 mesh. The particle size of the titanium dioxide powder is ≤0.3 μm.
[0017] As a preferred embodiment, the powder comprises titanium dioxide and talcum powder in a weight ratio of (10-13): (13-15).
[0018] As a preferred embodiment, the weight ratio of the titanium dioxide to the talc is 12:14.
[0019] Talc powder as a filler for polyurethane waterproof coatings can not only reduce the volume shrinkage of the coating during curing, improve the wear resistance and adhesion of the coating, reduce costs, but also make the coating have good storage stability.
[0020] As a preferred embodiment, the auxiliary agent includes, by weight, 0.1-1 part of a wetting and dispersing agent, 0.1-0.5 part of a defoaming agent, and 0.1-0.5 part of a leveling agent.
[0021] As a preferred embodiment, the auxiliary agent includes 0.5 parts of wetting and dispersing agent, 0.1 parts of defoaming agent and 0.2 parts of leveling agent in parts by weight.
[0022] As a preferred embodiment, the coupling agent is an epoxy-modified silane coupling agent, and the epoxy-modified silane coupling agent has a refractive index of 1.4-1.5 at 25°C and a specific gravity of 1.04-1.07 g / cm 3 .
[0023] The inventors further discovered that the urethane acrylate polymer and the epoxy-modified silane coupling agent can work together to further improve the adhesion to the glass substrate. The reason may be that the urethane acrylate polymer reacts with the epoxy-modified silane coupling agent and has good bonding strength. The epoxy-modified silane coupling agent has good affinity for silicon materials in the glass and can penetrate into the tiny pores on the glass surface to form a strong bonding layer, thereby improving the adhesion of the paint surface.
[0024] Coupling agent is an auxiliary agent to enhance the water resistance of the paint film and can only be added during construction. The paint with the coupling agent must be used up within 8 hours. If it is used after more than 8 hours, the paint may become rough, which may affect the paint effect and chemical resistance. BL-20 is the main curing resin in the formula, which directly determines the overall performance of the paint film and has good adhesion to the glass substrate.
[0025] As a preferred embodiment, the initiator is a photoinitiator, and the photoinitiator includes at least one of R-XBPO, GR-TPO, 184, TPO-L, and MBF.
[0026] As a preferred embodiment, the photoinitiator includes a combination of R-XBPO, GR-TPO, and 184.
[0027] As a preferred embodiment, the weight ratio of R-XBPO, GR-TPO, and 184 is (1-3): (1-2): (3-5).
[0028] As a preferred embodiment, the weight ratio of R-XBPO, GR-TPO, and 184 is 1.5:1:4.
[0029] The weight ratio of the epoxy-modified silane coupling agent of component A to component B of the present invention is 100:1. The obtained paint film has a fast drying speed, excellent adhesion and resistance, and is not easy to crack in the later stage. The reasons may be: if too much epoxy-modified silane coupling agent is added, the primer will be roughened, the toughness of the paint film will decrease, and it will be easy to crack in the later stage. If too little epoxy-modified silane coupling agent is added, the paint film will be viscous, the adhesion will deteriorate, and the resistance will decrease.
[0030] A second aspect of the present invention provides a method for preparing a UV-cured glass solvent-free spray-coated solid color primer, comprising the following steps:
[0031] S1: Mix the acrylic resin according to the weight ratio, then add the diluent, wetting dispersant, defoamer, titanium dioxide, disperse at low speed with a disperser, add the initiator while dispersing, and then disperse at high speed for 20-40 minutes until the fineness is ≤25μm;
[0032] S2 adds talcum powder and leveling agent and disperses at medium speed for 10-20 minutes to obtain component A;
[0033] Before coating S3, add component B and stir evenly before use.
[0034] As a preferred embodiment, the low-speed dispersion rate is 500-600 r / min, the high-speed dispersion rate is 1000-1200 r / min; and the medium-speed dispersion rate is 600-800 r / min.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) The UV-curable glass solvent-free spray-coated solid color primer of the present invention adopts a combination of polyurethane acrylate polymer, polyurethane acrylate oligomer and epoxy acrylate as the main curing resin to prepare a solid color primer with good adhesion to glass, water resistance and wear resistance, and has a fast curing speed and the paint film is not easy to crack in the later stage.
[0037] (2) The UV-curable glass solvent-free spray-coated solid color primer of the present invention, the polyurethane acrylate oligomer and the epoxy-modified silane coupling agent work together to further improve the adhesion to the glass substrate.
[0038] (3) The UV-cured glass solvent-free spray-coated solid color primer of the present invention has a weight ratio of 100:1 between component A and component B epoxy-modified silane coupling agent. The obtained paint film has a fast drying speed, excellent adhesion and durability, and is not prone to cracking in the later stage.
[0039] (4) The UV-curable glass solvent-free spray-coated solid color primer of the present invention has a fast curing speed and can be UV-cured at 40-50° C. for 5-7 minutes by infrared leveling.
[0040] (5) The UV-curable glass solvent-free spray-coated solid color primer of the present invention does not require solvent dilution during construction, has zero VOC emissions, and can be directly mechanically sprayed after only adding a coupling agent and stirring evenly. It can be cured in a few seconds under UV light, and the next step can be carried out immediately after sanding. The adhesion is stable, and the construction is not affected by the environment and season. DETAILED DESCRIPTION
[0041] Example 1
[0042] A UV-cured glass solvent-free spray-adhesive solid color primer, the preparation raw materials of which include component A and component B, wherein the preparation raw materials of component A include, by weight, 50.7 parts of acrylic resin, 16 parts of diluent, 26 parts of powder, 6.5 parts of initiator, and 0.8 parts of auxiliary agent; the component B includes at least a coupling agent.
[0043] The weight ratio of the component A to the component B is 100:1.
[0044] The acrylic resin includes a combination of difunctional polyurethane acrylate polymer, epoxy acrylate and difunctional polyurethane acrylate oligomer, with a weight ratio of 34.7:8:8. The difunctional polyurethane acrylate polymer was purchased from Juxinglong New Materials Co., Ltd., with a brand name of BL-20; the difunctional polyurethane acrylate oligomer was purchased from Changsha Guangxin New Materials Co., Ltd., with a brand name of LT-408; and the epoxy acrylate was purchased from Jiangsu Sanmu Chemical Co., Ltd., with a brand name of 6105-80.
[0045] The diluent is tripropylene glycol diacrylate, purchased from Changxing Chemical Industry (China) Co., Ltd.
[0046] The powder includes titanium dioxide and talc, with a weight ratio of 12:14. The talc has a particle size of 1250 mesh and is purchased from Tianze Superfine Talc Co., Ltd., with a brand name of WF-10-98Q / TZB. The titanium dioxide has a particle size of ≤0.3 μm and is purchased from Yibin Tianyuan Haifeng Hetai Co., Ltd., with a brand name of TYR-588.
[0047] The auxiliary agent includes 0.5 parts of wetting and dispersing agent, 0.1 parts of defoaming agent and 0.2 parts of leveling agent in parts by weight.
[0048] The wetting and dispersing agent is EFKA4010, the defoaming agent is EFKA2022, and the leveling agent is EFKA3777, all of which are purchased from BASF (China) Co., Ltd.
[0049] The coupling agent is an epoxy-modified silane coupling agent, with a refractive index of 1.4-1.5 at 25°C and a specific gravity of 1.04-1.07 g / cm 3 , purchased from Haimingsdeqian Chemical Co., Ltd., with the brand name Aberrant 1051.
[0050] The initiator includes a combination of R-XBPO, GR-TPO, and 184 in a weight ratio of 1.5:1:4.
[0051] The R-XBPO and GR-TPO were purchased from Hubei Gurun Technology Co., Ltd., and the 184 was purchased from Double Bond Chemical (Shanghai) Co., Ltd.
[0052] A method for preparing a UV-cured glass solvent-free spray-coated solid color primer comprises the following steps:
[0053] S1: Mix the acrylic resin according to the weight ratio, then add the diluent, wetting dispersant, defoamer, titanium dioxide, disperse at low speed with a disperser, add the initiator while dispersing, and then disperse at high speed for 30 minutes until the fineness is ≤25μm;
[0054] S2 added talcum powder and leveling agent to disperse at medium speed for 15 minutes to obtain component A;
[0055] Before coating S3, add component B and stir evenly before use.
[0056] As a preferred embodiment, the low-speed dispersion rate is 500 r / min, the high-speed dispersion rate is 1100 r / min, and the medium-speed dispersion rate is 700 r / min.
[0057] Example 2
[0058] A UV-cured glass solvent-free spray-adhesive solid color primer and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that the weight ratio of component A to component B is 100:2.
[0059] Example 3
[0060] A UV-cured glass solvent-free spray-adhesive solid color primer and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that the weight ratio of component A to component B is 100:0.5.
[0061] Comparative Example 1
[0062] Clivia H-7663PU primer.
[0063] Comparative Example 2
[0064] Clivia H-6161 water-based primer.
[0065] Comparative Example 3
[0066] Clivia H-7762 low temperature baking paint.
[0067] Performance Testing
[0068] The solid color primer prepared in Examples 1, 2, and 3 was mixed with the color paste in a weight ratio of 90:10, and the mixture was subjected to infrared leveling at 40-50°C for 7 minutes, and then UV cured with a curing energy of 350-600 mj / cm 2 , and cure for 5s. Adhesion test is level 0.
[0069] Example 2 The paint film is prone to cracking in the later stage (cracked after 48h of hot and cold cycle)
[0070] Under the same curing conditions as in Example 1, the paint surface of Example 3 was not dry and was sticky, and the adhesion was level 4.
[0071] Comparative Example 1 requires more than 4 hours to dry at room temperature, and the curing time is long.
[0072] Comparative Example 2 needs to be baked at 40-50°C for more than 4 hours, and the curing time is long.
[0073] Comparative Example 3 requires the addition of a certain amount of solvent for spraying, which causes environmental pollution.
Claims
1. A UV-cured glass solvent-free spray-coated solid color primer, characterized in that: The raw materials for preparation include component A and component B. The raw materials for preparation of component A include, by weight, 40-60 parts of acrylic resin, 10-20 parts of diluent, 20-30 parts of powder, 5-10 parts of initiator, and 0.1-1 part of auxiliary agent; the component B includes at least a coupling agent.
2. The UV-cured glass solvent-free spray-coated solid color primer according to claim 1, characterized in that: The weight ratio of the component A to the component B is 100:(0.5-2).
3. The UV-cured glass solvent-free spray-coated solid color primer according to claim 1, characterized in that: The acrylic resin includes one or a combination of polyurethane acrylate, epoxy acrylate, silicone-modified acrylate, and pure acrylate.
4. The UV-curable glass solvent-free spray-coated solid color primer according to claim 3, characterized in that: The polyurethane acrylate is a difunctional polyurethane acrylate, and the polyurethane acrylate includes a difunctional polyurethane acrylate oligomer and a difunctional polyurethane acrylate polymer.
5. The UV-cured glass solvent-free spray-coated solid color primer according to claim 4, characterized in that: The acrylic resin comprises a combination of a difunctional polyurethane acrylate polymer, epoxy acrylate and a difunctional polyurethane acrylate oligomer, with a weight ratio of (30-40): (5-10): (5-10).
6. The UV-cured glass solvent-free spray-coated solid color primer according to claim 1, characterized in that: The particle size of the powder is ≤1 μm; the powder is selected from at least one of silicon dioxide, titanium dioxide, talc and calcium oxide.
7. The UV-cured glass solvent-free spray-coated solid color primer according to claim 6, characterized in that: The auxiliary agent includes, by weight, 0.1-1 part of a wetting and dispersing agent, 0.1-0.5 part of a defoaming agent, and 0.1-0.5 part of a leveling agent.
8. The UV-curable glass solvent-free spray-coated solid color primer according to claim 1, characterized in that: The coupling agent is an epoxy-modified silane coupling agent, and the epoxy-modified silane coupling agent has a refractive index of 1.4-1.5 at 25° C. and a specific gravity of 1.04-1.07 g / cm 3 .
9. The UV-curable glass solvent-free spray-coated solid color primer according to claim 1, characterized in that: The initiator is a photoinitiator, and the photoinitiator includes at least one of R-XBPO, GR-TPO, 184, TPO-L, and MBF.
10. A method for preparing the UV-curable glass solvent-free spray-coated solid color primer according to any one of claims 7 to 9, characterized in that: The following steps are involved: S1: Mix the acrylic resin according to the weight ratio, then add the diluent, wetting dispersant, defoamer, titanium dioxide, disperse at low speed with a disperser, add the initiator while dispersing, and then disperse at high speed for 20-40 minutes until the fineness is ≤25μm; S2 adds talcum powder and leveling agent and disperses at medium speed for 10-20 minutes to obtain component A; Before coating S3, add component B and stir evenly before use.
Citation Information
Patent Citations
High-solid-content quick-drying water-based white primer and preparation method thereof
CN102643586A
A Tear-Resistant Solid-Color Primer for Exterior Walls and Its Preparation Method
CN115449296B
Protective coating for window glass
CN101218311A
Color UV curable coating dedicated for oil couplings / color wheels
CN103059716A
Ultraviolet curing coating for glass
CN106675377A